An approximation formula for Euler-Mascheroni's constant - Panzone, Pablo Andres (2016)
A fast approximation formula for Euler–Mascheroni’s constant based on a certain integral due to Peter Borwein is given. This asymptotic formula for γ involves harmonic numbers, ln 2 and rational numbers whose denominators are powers of 2.